KOMODIFIKASI TRADISI OMED-OMEDAN - Tri Lazuardi, I Nyoman Fizal; Erawan, I Ketut Putra; Ali Azhar, Muh. (Jurnal Nawala Politika, 2021)
This study describes the commodification of the Omed-omedan tradition in Banjar Kaja, Sesetan Village, Denpasar City. The problem discussed is the changes caused by commodification in economic, social, and political. In this study, qualitative method and the theory of commodification by Vincent Mosco which focuses on the change from use value to exchange value are used in analyzing data. The results showed that the commodification process based on the innovation of the Banjar Kaja Sesetan as the organizer of the Omed-omedan tradition with the aim of preserving traditions, creating cultural tourism destinations, obtaining economic benefits, building social capital, and building social relations. The impact of the commodification that occurs in the Omed-omedan tradition is able to influence the community life of the Banjar Kaja Sesetan, therefore it is maintained. Keywords: Commodification, Omed-Omedan Tradition, Economy, Social,Politics